Dibromocarbene functionalization of boron nitride nanosheets: Toward band gap manipulation and nanocomposite applications - COLEMAN, JONATHAN (My University, 2014)
We report the covalent functionalization of exfoliated boron nitride nanosheets (BNNSs) using dibromocarbene (DBC) species. The functionalization of BNNSs is enabled as the nanosheets are utilized as 2-dimensional (2-D) phase-transfer catalysts (PTC) for the migration of carbenes across the organic-aqueous phase boundary. We postulate that BNNSs stabilize carbenes by forming B-CBr2 ylides and in-turn act as the reaction substrate. DBC functionalization of BNNSs results in the formation of B-C and B-N bonds to the sp2 hybridized BNNS lattice via the formation of dibromo-bridged bicyclo BCN systems. The covalent functionalization was characterised using HR-TEM, AFM, EELS, XRD, EDX, ToF-SIMS, TGA, Raman, XPS, FTIR, and UV-Vis techniques. Utilization of CBr2 groups as a means by which BNNSs may be integrated and interfaced with solvents, molecular and condensed phase materials was demonstrated by grafting alkyl chains from the functional groups via alkyl/halogen exchange. Alkyl-functionalized BNNSs were integrated within polyethylene (LDPE) and extruded to form BNNS-nanocomposite fibres. Implications of the covalent functionalization of h-BN are considered in the context of band-gap manipulation and the versatility of the CBr2 functional groups to enable subsequent chemical derivatization.
PUBLISHED
Keywords: ToF-SIMS, TGA, Raman, XPS, FTIR, and UV-Vis techniques; ToF-SIMS, TGA, Raman, XPS, FTIR, and UV-Vis techniques